The Study on Training of University New Teachers in China - Zhu, Ming; Yang, Zezhong; Qu, Zhaohua; Wang, Tong (American Journal of Education and Learning, 2017)
In the era of higher education transforming from elite to popularization, universities introduced large-scale highly educated talents as new teachers. These new teachers own rich theoretical knowledge, and lack teaching skills. In order to improve their teaching professional development, a series of related studies appeared and had gained a lot of research results over the past decades. This paper reviewed these studies and summarized its training contents and methods, and gave the suggestions about further study.